Myeloid sarcoma in the tongue - Bernar Monteiro Benites; Felipe Paiva Fonseca; Wanessa Miranda-Silva; Julia Stephanie Bruno; Luciana Tucunduva; Eduardo Rodrigues Fregnani (University of São Paulo, 2021)
Leukemic cells are rarely present in the oral cavity, and there are very few reports regarding such cases. However, we identified some reports of leukemic cells infiltrating tissues in the oral cavity, including gingival involvement. Recurrent painful oral ulcerations and prominent generalized periodontal destruction are the most common oral features of neutrophil disorders, and they may even be the initial symptoms of the disease. The ulcers may affect any part of the oral mucosa, including the tongue and palate. The objective of this report is to describe and discuss a case of myeloid sarcoma in the oral cavity of a 48-year-old male patient.